HAK ASUH ANAK BELUM MUMAYYIZ DALAM PUTUSAN PENGADILAN AGAMA (STUDI KOMPARATIF PUTUSAN PENGADILAN AGAMA PALU DAN PUTUSAN PENGADILAN AGAMA BANDUNG) - Izza, Sabila; Hasanah, Idaul; Arif Zuhri, Muhammad (Program Studi Hukum Keluarga Islam, 2025)
The focus of this article is comparing two different religious court decisions in child custody lawsuits. This article aims to identify similarities and differences in judges' considerations in these decisions, why judges have different decisions in the same case. This article uses a normative juridical method with a case approach and comparison of two first instance religious court decisions. The results of the article show several differences in the legal basis used by judges in handing down a decision. These differences include legal facts, juridical and non-juridical considerations, the judge's interpretation, and the final decision. In handling custody cases of children who are not yet mumayyiz due to divorce, one cannot only be guided by the Child Protection Law and the Compilation of Islamic Law, but it is also necessary to consider other factors such as the condition of the parents, the economy and the emotional closeness between the child and the parents.